The individuation of mere entelechies in Leibniz - Marques, Edgar (Cadernos Espinosanos, 2023)
In this article, I analyze and criticize the solution presented by Robert Brandom to the problem formulated by him about the criterion of distinctiveness of perceptions present in mere entelechies. Brandom considers the link between distinction and consciousness made by several Leibniz interpreters to be problematic, with the purpose of accounting for the different degrees of distinction of perceptions, since such link can only be valid for souls and spirits, not applying to entelechies, which are not endowed with any kind of sentience or reflection. As a result, Brandom proposes an interpretation that would not have this difficulty. According to this proposal, a perception will be more distinct the greater its expressive domain, that is, its degree of distinction will be determined by the number of inferences that can be made from it. Thus, according to him, it becomes possible to compare different perceptions and order them in a series that goes from the least distinct to the most distinct based on their respective expressive domains. I show in this article that both this – in my view, apparent – problem raised by Brandom and the solution proposed by him stem from a partial and mistaken understanding of Leibniz’s theory of monads, in such a way that we would be facing here a false solution addressed to a non-existent problem.